Emerging Concept: ‘Central Benefit Model’ of Exercise in Falls Prevention - Liu-Ambrose, Teresa (Br J Sports Med, 2012)
Falls are a common geriatric syndrome and are the third leading cause of chonic disability worldwide. Falls are not random events and occur, at least in part, due to impaired physiological function, such as impaired balance, and cognitive impairment. The clinical syndrome of falls is important for sports and exercise medicine clinicians as there is Level 1 evidence that targeted exercise prescription is an effective intervention strategy. The widely accepted dogma is that improved physical function, balance and muscle strength, underlies the effectiveness of the exercise in reducing falls. However, findings from randomized controlled trials suggest that exercise reduce falls via mechanisms other than improved physiological function. We propose that improved cognitive function – specifically, executive functions – and associated functional plasticity may be an important yet under-appreciated mechanism by which the exercise reduces falls in older adults.